Symmetric Functions for the Generating Matrix of the Yangian of gl_n(C) - Rozhkovskaya, Natasha (The Electronic Journal of Combinatorics, 2009)
Analogues of classical combinatorial identities for elementary and homogeneous symmetric functions with coefficients in the Yangian are proved. As a corollary, similar relations are deduced for shifted Schur polynomials.